Mixture design for evaluation of potassium sorbate and xanthan gum effect on properties of tapioca starch films obtained by extrusion - Flores, Silvia Karina (2010)
A mixture experimental design was used to study the physical and microbiological properties of tapioca starch-glycerol based edible films added with xanthan gum (XG) and potassium sorbate (PS) and obtained by extrusion technology. The results showed that PS presence decreased the ultimate tensile strength and elastic modulus and increased strain at break. XG produced a reinforcing effect on the films and also enhanced solubility in water and decreased moisture content. The analysis revealed significant interactions between components in the mixture. The water vapor permeability values ranged from 3.72 × 10- 10 to 6.4 × 10- 10 g/m s Pa. The PS concentration was not affected by the extrusion process and the preservative was available to act as an antimicrobial agent. Extruded films made from biopolymers showed a potential application in food technology as an active packaging.